Interannual Variability of Winter Rainfall in Upper Myanmar - Oo, Kyaw Than (Journal of Sustainability and Environmental Management, 2022)
Upper Myanmar region, roughly located between 21° 00' N and 28° 30' N latitude and 92° 10' E and 101° 11' E longitude, is the place where the winter cold season contributes 2% of the annual total rainfall. The rainfall associated with Western disturbances is small in quantum but veritably important for the cold season crops, maintaining the glaciers over the Putao region, hydropower generation for the whole country and hazard of Jade mining of the Upper Myanmar area. This study aims to find interannual variability and related ocean-atmospheric pattern link with Upper Myanmar cold season rainfall by using great-resolution reanalysis data (ERA5) during 1990-2020. Correlation analysis to test the validation of ERA5 gridded data with the observed data from 25 stations across Myanmar, showed a strong correlation value in the same period that enough reliable for best analysis results. An anomalous anticyclonic (cyclonic) circulation persists over the southern part of the Bay of Bengal and South China sea during wet (dry) years. Also, the warming over the Indian Ocean and the cooling over the Tibetan plateau region correspond to south-north transport of moisture, ensuing in positive rainfall anomalies over the study region during winter. The wide patches of strong negative (positive) correlation are found over the Pacific Ocean, the Atlantic Ocean, Mediterranean Sea (MED), Arabian Sea (ARS), and Red Sea (RED) during wet (dry) years. The link implies that NPO, SPO, and MED have an impact on the winter rainfall inter-annual variability. In addition, the cooling (warming) over the Indochina and western Pacific regions influences the Hadley and Walker circulation bringing above (below) normal rainfall, respectively, over Upper Myanmar. The reply of indices (PO, MED, NINO3.4, IOD, and WDs) on winter rainfall, necessary to further investigation. The complete analysis of winter rainfall aids in the understanding of past extreme events as well as the forecasting and monitoring of drought and floods in Upper Myanmar.